2018
DOI: 10.1097/gox.0000000000001759
|View full text |Cite
|
Sign up to set email alerts
|

Perforator Propeller Flaps for the Coverage of Middle and Distal Leg Soft-tissue Defects

Abstract: Background:Local propeller flaps preserve the main vascular arteries of the lower extremity and muscle function, avoiding the need for a microsurgical anastomosis and the benefit of providing a “like with like” coverage. Our goal in this study was to demonstrate the versatility, safety, and complications of the local propeller flaps for lower extremity reconstruction.Methods:We present a series of 28 patients in whom we used local propeller flaps to restore small-to-medium soft-tissue defects of the lower limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 23 publications
3
48
0
4
Order By: Relevance
“…Mendieta et al reported that they used PTAPF in 14 of 28 patients with lower extremity soft tissue defects after trauma. They observed partial flap necrosis in 3 patients in their series and all the partial flap necrosis were observed in PTAPF group …”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Mendieta et al reported that they used PTAPF in 14 of 28 patients with lower extremity soft tissue defects after trauma. They observed partial flap necrosis in 3 patients in their series and all the partial flap necrosis were observed in PTAPF group …”
Section: Discussionmentioning
confidence: 89%
“…They observed partial flap necrosis in 3 patients in their series and all the partial flap necrosis were observed in PTAPF group. 2 The planning of the flaps outside the zone of injury is an important factor for the flap viability in reconstruction of high-energy injuries, and the risk of perforator F I G U R E 4 A, Preoperative X-ray and B, preoperative picture of the 39-year-old female patient with exposed plaque over the medial malleolar region after trimalleolar fracture surgery. C, Elevation of the flap over tibialis posterior artery perforator pedicle adjacent to the defect area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Los defectos de cobertura en el miembro inferior, particularmente en la pierna, son un problema difícil de solucionar, debido a las características propias de la región anatómica, como la presencia de prominencias óseas, la escasez de tejidos blandos y la elasticidad limitada de la piel. 1,2 En el pasado, las alternativas reconstructivas locales eran los colgajos de gastrocnemio y sóleo, y su uso estaba limitado al tercio proximal y medio de la pierna; 3 la reconstrucción del tercio distal de la pierna quedaba supeditada a opciones complejas, como un colgajo cross-leg o un colgajo microquirúrgico, 2,4 ambos procedimientos no exentos de complicaciones y con fracasos del 15 al 20%. 5 A su vez, es importante destacar que no todos los pacientes tienen condiciones óptimas para aplicar estos procedimientos, lo que, sumado a su complejidad, dificultan su realización.…”
Section: Introductionunclassified